2018
DOI: 10.1101/313767
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Substrate binding allosterically relieves autoinhibition of the TRIB1 pseudokinase

Abstract: Abstract:The Tribbles family of pseudokinases recruit substrates to the COP1 ubiquitin ligase for ubiquitination. CCAAT-enhancer binding protein (C/EBP) family transcription factors are crucial Tribbles substrates in adipocyte and myeloid development. Here we show that the TRIB1 pseudokinase can recruit various C/EBP family members, with binding of C/EBPβ attenuated by phosphorylation. To explain the mechanism of substrate recruitment, we solved the crystal structure of TRIB1 in complex with C/EBPα. TRIB1 unde… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Although many studies confirmed the importance of protein-protein interaction in Tra1/TRRAP function, mutational analyses of S. cerevisiae Tra1 indicated that its pseudokinase domain has also critical roles in vivo [25][26][27]. Similarly, recent work established that the atypical sequence of the TRIB pseudokinase domain relates to an important functional fold, whose plasticity modulates substrate ubiquitination or assembly of signaling modules [28][29][30].…”
Section: The Tra1/trrap Pseudokinasementioning
confidence: 99%
“…Although many studies confirmed the importance of protein-protein interaction in Tra1/TRRAP function, mutational analyses of S. cerevisiae Tra1 indicated that its pseudokinase domain has also critical roles in vivo [25][26][27]. Similarly, recent work established that the atypical sequence of the TRIB pseudokinase domain relates to an important functional fold, whose plasticity modulates substrate ubiquitination or assembly of signaling modules [28][29][30].…”
Section: The Tra1/trrap Pseudokinasementioning
confidence: 99%
“…This has been observed with mutations, where a compound was able to compete with the ATP or induce an allosteric change of the kinase pocket (7,8). Many examples have been described in different solid tumors, and many of these therapies have reached the clinical setting (9)(10)(11)(12)(13)(14)(15)(16)). Similar findings have been observed with the amplification of genes that code for proteins with a relevant role in cell signaling, like HER2 in BC (17,18).…”
Section: Introductionmentioning
confidence: 99%